PENYULUHAN KESEHATAN TENTANG PEMBERIAN ASI EKSKLUSIF SEBAGAI SALAH SATU TINDAKAN PENCEGAHAN STUNTING - Yulaikah, Siti; Susilowati, Dewi (Jurnal Abdi Insani, 2025)
Nearly 9 million or around 37% of children under five in Indonesia are stunted. Indonesia is the country with the fifth largest prevalence of stunting worldwide (Basic Health Research, 2013). Intervention for children with stunting requires the convergence of programs or interventions and synergistic efforts from ministries or institutions, local governments, and the business world or the community. The benefits of breastfeeding at the beginning of a baby's life as the beginning of stunting prevention need to always be socialized to the community both through counseling, leaflets, banners, posters, advertisements and so on. This is used to support the improvement of public knowledge, especially mothers to support exclusive breastfeeding. This research is expected to be able to increase the knowledge of pregnant women about the importance of exclusive breastfeeding as one of the stunting prevention measures. The method of activities in Community Service uses the method of lectures, discussions or questions and answers demonstration and simulation or practice. This outreach activity in the form of Community Service was carried out for 2 days, Thursday – Friday, April 25 – 26 2024, 07.30. WIB until the end took place at the Granting Jogonalan Klaten village hall which is the working area of ​​the Jogonalan 2 Klaten Community Health Center with approximately 26 participants attending. There was an increase in knowledge among mothers, this can be seen from the scores between the pre-test and post-test given to participants.